Irrigação por aspersão em arroz: avaliação econômica, uso da água e rendimento de grãos em resposta à disponibilidade hídrica - Tonetto, Felipe (2024)
Sprinkler rice cultivation is an alternative to continuous flooding (CF), due to its lower water consumption and lower operating costs, especially in terms of soil preparation and labor. However, maintaining growth and yield parameters at levels close to those of the CF is the main factor to be overcome. Therefore, the timing of irrigation and the frequency of irrigation need to be investigated to help growers make the decision to switch from a well-known and highly productive system to one that is still little used in rice. Therefore, the timing of irrigation and the frequency of irrigation need to be investigated to help growers make the decision to switch from a well-known and highly productive system to one that is still little used in rice. Among these challenges are studies to calibrate crop coefficients and determine the most appropriate irrigation management to achieve high yields with low water consumption. Furthermore, experiments were conducted during the 2020/21, 2021/22 and 2022/23 harvests to determine the water requirement and derive the crop coefficients of aerobic rice, evaluate the growth parameters, water and crop productivity, and return of rice grown under sprinklers. Two lowland rice cultivars (IRGA-424 RI and IRGA-431 CL) were subjected to three irrigation managements: (i) daily irrigations; (ii) alternating irrigations and (iii) rainfed. Soil moisture measurements were taken throughout the cycle. Growth parameters were assessed at certain stages of the cycle. The basal crop coefficient (Kcb) calibrated by the SIMDualKc model was 0.15, 1.08 and 0.80, while the crop coefficients (Kc) were 0.72, 1.13 and 0.95 for the early, middle, and late stages, respectively. The Kcact values for sprinkler-irrigated rice were higher than for rainfed rice, especially in the middle phase (Kc act mid = 1.13 vs 0.82). Rice yields were 7,600 (±1,400) and 7,200 (±1,800) kg ha-1 , with daily and alternate irrigation, respectively. Crop evapotranspiration was 694 (±20) and 450 mm for irrigated and rainfed crops, respectively. Growth and yield parameters were affected by water deficit, but not by irrigation management. ID and IA management provided the producer with an operating profit.